Breathing Abnormalities During Sleep and Wakefulness in Rett Syndrome: Clinical Relevance and Paradoxical Relationship With Circulating Pro-oxidant Markers - Leoncini, Silvia; Signorini, Cinzia; Boasiako, Lidia; Scandurra, Valeria; Hayek, Joussef; Ciccoli, Lucia; Rossi, Marcello; Canitano, Roberto; De Felice, Claudio (Frontiers in Neurology, 2022)
Background Breathing abnormalities are common in Rett syndrome (RTT), a pervasive neurodevelopmental disorder almost exclusively affecting females. RTT is linked to mutations in the methyl-CpG-binding protein 2 (MeCP2) gene. Our aim was to assess the clinical relevance of apneas during sleep-wakefulness cycle in a population with RTT and the possible impact of apneas on circulating oxidative stress markers. Methods Female patients with a clinical diagnosis of typical RTT (n = 66), MECP2 gene mutation, and apneas were enrolled (mean age: 12.5 years). Baseline clinical severity, arterial blood gas analysis, and red blood cell count were assessed. Breathing was monitored during the wakefulness and sleep states (average recording time: 13 ± 0.5 h) with a portable polygraphic screening device. According to prevalence of breath holdings, the population was categorized into the wakefulness apnea (WA) and sleep apnea (SA) groups, and apnea-hypopnea index (AHI) was calculated. The impact of respiratory events on oxidative stress was assessed by plasma and intra-erythrocyte non-protein-bound iron (P-NPBI and IE-NPBI, respectively), and plasma F2-isoprostane (F2-IsoP) assays. Results Significant prevalence of obstructive apneas with values of AHI > 15 was present in 69.7% of the population with RTT. The group with SA showed significantly increased AHI values > 15 (p = 0.0032), total breath holding episodes (p = 0.007), and average SpO2 (p = 0.0001) as well as lower nadir SpO2 (p = 0.0004) compared with the patients with WAs. The subgroups of patients with WA and SA showed no significant differences in arterial blood gas analysis variables (p > 0.089). Decreased mean cell hemoglobin (MCH) (p = 0.038) was observed in the group with WAs. P-NPBI levels were significantly higher in the group with WA than in that with SAs (p = 0.0001). Stepwise multiple linear regression models showed WA being related to nadir SpO2, average SpO2, and P-NPBI (adjusted R2 = 0.613, multiple correlation coefficient = 0.795 p < 0.0001), and P-NPBI being related to average SpO2, blood PaCO2, red blood cell mean corpuscular volume (MCV), age, and topiramate treatment (adjusted R2 = 0.551, multiple correlation coefficient = 0.765, p < 0.0001). Conclusion Our findings indicate that the impact of apneas in RTT is uneven according to the sleep-wakefulness cycle, and that plasma redox active iron represents a potential novel therapeutic target.